Critical role of RAGE and HMGB1 in inflammatory heart disease - Bangert, Anna; Andrassy, Martin; Müller, Anna-Maria; Bockstahler, Mariella; Fischer, Andrea; Volz, Christian H.; Leib, Christoph; Göser, Stefan; Korkmaz-Icöz, Sevil; Zittrich, Stefan; Jungmann, Andreas; Lasitschka, Felix; et al. (Proceedings of the National Academy of Sciences - PNAS, 2016)
Autoimmune response to cardiac troponin I (TnI) induces inflammation and fibrosis in the myocardium. High-mobility group box 1 (HMGB1) is a multifunctional protein that exerts proinflammatory activity by mainly binding to receptor for advanced glycation end products (RAGE). The involvement of the HMGB1–RAGE axis in the pathogenesis of inflammatory cardiomyopathy is yet not fully understood. Using the well-established model of TnI-induced experimental autoimmune myocarditis (EAM), we demonstrated that both local and systemic HMGB1 protein expression was elevated in wild-type (wt) mice after TnI immunization. Additionally, pharmacological inhibition of HMGB1 using glycyrrhizin or anti-HMGB1 antibody reduced inflammation in hearts of TnI-immunized wt mice. Furthermore, RAGE knockout (RAGE-ko) mice immunized with TnI showed no structural or physiological signs of cardiac impairment. Moreover, cardiac overexpression of HMGB1 using adeno-associated virus (AAV) vectors induced inflammation in the hearts of both wt and RAGE-ko mice. Finally, patients with myocarditis displayed increased local and systemic HMGB1 and soluble RAGE (sRAGE) expression. Together, our study highlights that HMGB1 and its main receptor, RAGE, appear to be crucial factors in the pathogenesis of TnI-induced EAM, because inhibition of HMGB1 and ablation of RAGE suppressed inflammation in the heart. Moreover, the proinflammatory effect of HMGB1 is not necessarily dependent on RAGE only. Other receptors of HMGB1 such as Toll-like receptors (TLRs)may also be involved in disease pathogenesis. These findings could be confirmed by the clinical relevance of HMGB1 and sRAGE. Therefore, blockage of one of these molecules might represent a novel therapeutic strategy in the treatment of autoimmune myocarditis and inflammatory cardiomyopathy.